Rotulagem nutricional: percepção do consumidor - Queiroz, Anne Caroline Duarte de (2023)
Nutritional labeling is a tool that stands out for helping consumers make healthy food choices. The present study is one of the first to evaluate the perception of clinical patients regarding changes to the new nutritional labeling and, consequently, their impact on food choices. This is a quantitative and descriptive cross-sectional study, with the participation of 40 individuals selected through convenience sampling. Data were collected through the application of a questionnaire aimed at clients of the Integrated Nutritional Service Center (NIAN), linked to the Department of Nutrition of the Federal University of Rio Grande do Norte (UFRN), during the months of August to October 2023, and analyzed using the RStudio program (version RStudio 2022.12.0+353). The habit of reading food labels was reported by half of the population. The level of education, family income and the need to select foods or diet specifically influenced the understanding, knowledge, use and trust in the information presented on the labels. Small-print on food labels and the use of technical terms were identified as the main factors that make reading and understanding difficult. Nutritional quality is considered the information that most influences when purchasing food products; and the expiration date for those who are not in the habit of reading labels. In conclusion, was observed that understanding the information on labels favors the habit of reading and its use in the selection of food products. Even with all the efforts of governments to popularize the understanding and use of nutritional labeling, there is still a lot of confusion, making it necessary to increase food and nutritional education actions in all lines of nutrition care.